Aplikasi Pengolahan Limbah Batik Menggunakan Membran Keramik Berbiaya Rendah pada Kolom Batch - Sarah Fiebrina Heraningsih; Oki Alfernando; Josua Sidauruk; Jesika Sinaga; Dinda Bectari; Enita Pitri; Fitri Nor Chasanah; Gabriel Adi Pratama Marpaung; Kasmiyanti Kasmiyanti; Maulidini Nabila; Mela Mauliani; Nur Sri Wahyuningsih; Riska Nofia Qona'a; Syafhira Putri Aulia (Jurnal Daur Lingkungan, 2023)
Batik is a characteristic of Indonesian culture which in the manufacturing process will produce waste as a residue from the colouring process. The waste still has a high colour content so if it is not processed further it will pollute the environment. This study aims to synthesize ceramic membranes from low-cost materials and apply the use of these membranes to treat batik waste in a batch column. The variable used in this study is the processing cycle, the results of the first processing are put back into the batch column for up to 3 iterations. The parameters tested were pH, turbidity and colour testing. The results showed that the ceramic membrane was able to treat batik wastewater with a maximum turbidity rejection % of 86.67 % and a maximum % rejection of 67.51 %. Low-cost ceramic membranes are effective for use as an alternative for batik waste treatment.